2009
DOI: 10.4049/jimmunol.0900452
|View full text |Cite|
|
Sign up to set email alerts
|

SP-A Preserves Airway Homeostasis During Mycoplasma pneumoniae Infection in Mice

Abstract: The lung is constantly challenged during normal breathing by a myriad of environmental irritants and infectious insults. Pulmonary host defense mechanisms maintain homeostasis between inhibition/clearance of pathogens and regulation of inflammatory responses that could injure the airway epithelium. One component of this defense mechanism, surfactant protein-A (SP-A), exerts multifunctional roles in mediating host responses to inflammatory and infectious agents. SP-A has a bacteriostatic effect on Mycoplasma pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 46 publications
3
31
1
Order By: Relevance
“…For in vivo infection, adherent Mp were washed by centrifuging at 6000 rpm for 5 minutes and resuspended in sterile saline for infection at a concentration of 1 × 10 8 Mp/50 μl inoculum. Mp burden was assessed as previously described by plating BAL or by RT-PCR using primers against Mp-specific P1-adhesin gene relative to the housekeeper cyclophilin (6). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For in vivo infection, adherent Mp were washed by centrifuging at 6000 rpm for 5 minutes and resuspended in sterile saline for infection at a concentration of 1 × 10 8 Mp/50 μl inoculum. Mp burden was assessed as previously described by plating BAL or by RT-PCR using primers against Mp-specific P1-adhesin gene relative to the housekeeper cyclophilin (6). …”
Section: Methodsmentioning
confidence: 99%
“…Indeed, studies have demonstrated that surfactant protein A (SP-A) binds Mp though disaturated phosphatidylglycerols and through a specific surface binding protein, MPN372 (4, 5) and limits the growth of Mp in vitro (5). SP-A also helps maintain airway homeostasis and reduce hyperresponsiveness by curtailing an overly-ambitious pro-inflammatory immune response during Mp infection in mice in vivo (6). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, mice infected with Eap Ϫ S. aureus that is not recognized by SP-A displayed impaired killing and persistent infection in association with elaboration of low but unsustainable levels of TNF␣, more intense neutrophilic inflammation, and delayed repopulation of the lung with macrophages. Previous studies reported that SP-A mediates both clearance and restoration of alveolar immune homeostasis in mice infected with Mycoplasma pneumoniae (83). However, the relative importance of SP-A binding to macrophages or bacteria has not been clear because SP-A may have indirect activities on macrophages.…”
Section: Cd11cmentioning
confidence: 99%
“…In contrast, SP-A and SP-D suppress secretion of pro-inflammatory cytokines and oxidant intermediates when macrophages are challenged with pathogen-derived cell wall components such as lipopolysaccharide [121,[138][139][140][141][142][143][144] or mycobacterial cell wall extract [145]; this protective SP-A function has been noted in both in vitro macrophage culture and in vivo animal models [58,140,146]. SP-A initially enhances clearance of Mycoplasma pneumoniae [133,134] but subsequently turns off inflammation [146], indicating that SP-A works in a temporal fashion to resolve inflammation. In this context, SP-A and SP-D regulate phagocytosis of apoptotic cells [147,148].…”
Section: Sp-a and Sp-dmentioning
confidence: 99%